Understanding the role of invictus games in supporting the transition for UK disabled military veterans - Mackintosh, Chris; Reavill, Niamh; O'Hanlon, Rebecca; Roberts, Dan (Frontiers in Sports and Active Living, 2025)
This study explores the experiences of veterans with disabilities regarding how sport and physical activity (PA) impacted their transition into civilian life. The study sought to understand how veterans' experiences since injury affect their well-being, independence, and future. Eight veterans (five women) with a physical disability were recruited via the Wounded, Injured and Sick (WIS) Invictus Games Foundation page. The qualitative semi-structured interviews studied their experience in sport and PA and transitioning out of the Armed Forces. Data were analysed using narrative analysis. Caddick's theoretical framework was used to explore and analyse the presence of five core veteran narratives in distinct narrative types; “struggling against decline”, “minimization”, “victimhood”, “life-as-normal” and “dramatic overcoming”. A further novel narrative was also heard, referred to as type, which was previously absent, emerged in the data, due to the age and competitiveness of the participants. This novel narrative, was referred to as “getting on with it” and was also found to be prominent in the data. The study provides insight into the experiences of veterans with disabilities and the role of sport and PA in their transition into civilian life. The findings suggest that promoting sport and PA and providing opportunities for participation in sporting events can be an effective tool in supporting veterans, providing recommendations for future work around disabled veterans engagement in sport and physical activity, specifically Invictus Games (IG) global event movement.